On-farm agrobiodiversity measurement and conservation - Joshi, Bal Krishna; Ghimire, Krishna Hari; Gurung, Rita; Pudasaini, Niranjan; Pant, Saroj; Paneru, Pragati; Gauchan, Devendra; Mishra, Krishna Kumar; Jarvis, Devra I. (NAGRC, 2020)
Total agrobiodiversity of any area is necessary to plan the implementation of agricultural and environmental projects and activities. Diversity is most for advancing agriculture development, however, modern agriculture has accelerated the replacement of old age crop diversity. Agrobiodiversity index and measures are commonly used and estimated for crop and animal species, landraces and sites. These are useful for locating sites, crops and custodians of agrobiodiversity. Agrobiodiversity includes crop and plant; livestock and fish, insect and microbial genetic resources that are cultivated, semi domesticated or wild. Diversity are ated properly that leads to choose the conservation approaches effectively.